ANALISIS JENIS DAN KADAR RESIDU ANTIBIOTIK PENISILIN PADA DAGING DAN HATI AYAM BROILER DI KECAMATAN SOBANG KABUPATEN PANDEGLANG - Dadan Ahmad Hudaya; Desi Trisnawati; Eko Yuniarsih; Reska Yasin Muttaqien (International Journal Mathla’ul Anwar of Halal Issues, 2026)
The increasing production of broiler chickens has encouraged the use of antibiotics in intensive farming systems, which may lead to antibiotic residues in animal products if withdrawal time is not properly implemented. This study aimed to analyze the types of antibiotics used and to determine the levels of penicillin residues in broiler chicken meat and liver in Sobang District, Pandeglang Regency. The research was conducted through field observation, farmer interviews, sample collection from three broiler farms, and laboratory analysis using the Enzyme Linked Immunosorbent Assay (ELISA) method. The results showed that all farms used β-lactam antibiotics, particularly amoxicillin, with some administration occurring close to the harvesting period. Penicillin residues were detected in most liver and meat samples. Residue levels in liver ranged from 0.568 to 1.076 mg/kg, while those in thigh meat ranged from 0.3707 to 1.155 mg/kg. These values exceeded the maximum residue limit of 0.1 mg/kg established by the Indonesian National Standard (SNI 01-6366-2000). The average residue concentration in liver was higher than in meat, indicating accumulation in metabolic organs. These findings suggest that the implementation of withdrawal time and antibiotic usage recording at the farm level has not been optimal. The study highlights the need to strengthen food safety–based production management to control antibiotic residues and to support antimicrobial resistance mitigation efforts.